Improvement facial aesthetics with immediate denture treatment - Budi Santosa, I Ketut; Rostiny, Rostiny; Djulaeha, Eha (Indonesian Journal of Dental Medicine, 2018)
Background: immediate dentures are one of denture treatment that provides a rapid treatment stage to improve aesthetics without patients experiencing toothless phase due the tooth is extraction or decaputated. Purpose: To reported maxillary immediate partial denture and mandibulary immediate complete overdenture with magnetic retention to improve facial aesthetics. Case: A-56 years old woman with twelve tooth loss (17,16,15, 26,34,35,36,37,44,45,46,47) and have fillings teeth on 21,11 and 12 patched in dental artisans less more than 1 year and now its felt swollen with mobility 30 in the last few weeks and teeth 31,41,42,43 experienced mobilitys 20 due to calculus and teeth 32,33 were deep caries with mobility 30. Case Management: in phanoramic photo teeth 11,21 and 22 saw a large periapical lesion í˜ 10mm and its advised to extract. In 32 and 33, non-immediate extraction was performed because periapical lesions and deep caries are large enough with the presence of periapical abscesses, while teeth 31, 41, 42 and 43 are scaling and rootplaning then endodontic treatment is performed to obtain a harmonious relationship between the upper anterior teeth and below the teeth 31,41.42.43 is immediately decaputated and restored with GI cement on the surface of the teeth and magnet keeper coping was done for 43. Discussion: The main objective of the immediate denture treatment is to avoid psychological, social and discomfort  from  look toothless Conclusion: Immediate denture is the choice of treatment  to improve the retention and facial aesthetic.